Analisis Putusan Hakim Terhadap Perkara Nomor 71/Pdt.G/2017/Pn.Jmb Mengenai Kasus Perjanjian Sogok-Menyogok - Ilham Satria; Diana Amir (Zaaken: Journal of Civil and Business Law, 2022)
The purpose of this research is to find out and analyze the agreement between the parties in the case decision No.71/Pdt.G/2017/PN.JMB based on the bribe agreement and reciprocal agreement. The research method used is a normative juridical research method with a statutory approach, a conceptual approach, and a case approach to the Civil Case Decision Number 71/Pdt.G/2017/PN.JMB. The research result of this thesis shows that the judge in his consideration stated that the agreement in this case was a reciprocal agreement to carry out the management of civil servants. Based on Article 1320 regarding the terms of the validity of the agreement in relation to the reciprocal agreement to carry out the management of this PNS, this agreement does not fulfill the legal requirements of the agreement, namely the objective conditions of a cause that is not prohibited, so this agreement of reciprocity is null and void by law. Judging from the efforts to fulfill the bribery agreement in this case, this case did not happen because the Defendant was unable to fulfill his promise to enroll the Plaintiff's younger brother as a civil servant and did not know the authorized official who received the bribe in this agreement. In this case the judge held the view that there was a legal consequence arising from a reciprocal agreement to administer civil servants by stating in his consideration that the Defendant did not have good faith. Abstrak Tujuan Penelitian ini adalah untuk mengetahui dan menganalisis Perjanjian antara para Pihak dalam Putusan Perkara No.71/Pdt.G/2017/PN.JMB Berdasarkan Perjanjian Sogok-Menyogok dan Perjanjian Timbal Balik. Metode penelitian yang digunakan adalah metode penelitian yuridis normatif dengan pendekatan perundang-undangan, pendekatan konsep, dan pendekatan kasus Putusan Perkara Perdata Nomor 71/Pdt.G/2017/PN.JMB. Hasil penelitian dari artikel ini menunjukkan bahwa hakim dalam pertimbangannya menyatakan perjanjian pada perkara ini merupakan perjanjian timbal balik untuk melakukan pengurusan PNS. Berdasarkan Pasal 1320 mengenai syarat sahnya perjanjian dikaitkan dengan perjanjian timbal balik untuk melakukan pengurusan PNS ini, maka perjanjian ini tidak memenuhi syarat sahnya perjanjian yaitu syarat objektif suatu sebab yang tidak terlarang, sehingga perjanjian tibal balik ini batal demi hukum. Dilihat dari upaya pemenuhan terhadap perjanjian sogok-menyogok pada perkara ini tidak terlaksana karena Tergugat tidak dapat memenuhi janjinya untuk memasukan adik Pengugat menjadi PNS dan tidak diketahuinya Pejabat yang berwenang yang menerima uang sogok pada hubungan perjanjian ini. Pada perkara ini hakim memiliki pandangan mengenai adanya suatu akibat hukum yang timbul dari perjanjian timbal balik untuk melakukan pengurusan PNS dengan menyatakan dalam pertimbangannya bahwa Tergugat tidak mempunyai etikad baik.